ANALISIS BIBLIOMETRIK (2014-2023): TREN LEAN MANUFACTURING DI SCIENCEDIRECT DENGAN VOSVIEWER - Nurlaila, Qomarotun; Putri, Nilda Tri; Amrina, Elita (Fakultas Teknik, Universitas Riau Kepulauan, 2023)
Research on the topic of lean Manufacturing (LM) has a good trend at the international level. Bibliometric analysis with VOSviewer has been widely applied by researchers to see research trends in a topic, quantitatively assess the current status and quickly identify future research directions based on unique publication parameters. Bibliometric analysis was conducted on 548 articles from ScienceDirect for the topic of LM in the period 2014 to 4 June 2023. From 29 journals it detected the names of journals that frequently published and names of journals that provided opportunities for authors to submit articles. Detected 1449 authors, 591 were the main authors and 858 were co-authors. The majority of the top-30 productive researchers are co-authors. Detected 53 names of countries of the main author, 8 countries that occupy the top-10 are developed countries and only 2 countries are developing countries. In writing articles, the author has a majority team of 2-4 people in one team. Based on the results of the VOSviewer mapping, there is a novelty in research for the keywords additive manufacturing and OEE. Recommendations for further research are that LM research carries manufacturing, focusing on engine performance using OEE indicators and the industry 4.0 approach.